Application of Mini-Nutritional Assessment (MNA) in Cancer Patients - A systematic Overview of Primary Studies - Torbahn, Gabriel; Strauß, Thomas; Sieber, Cornel; Volkert, Dorothee; Kiesswetter, Eva (SPRINGER, 2018)

Application of the "Geriatic 8 Screening Tools" (G8) in Female Cancer Patients - a systematic Review of Primary Studies - Strauß, Thomas; Torbahn, Gabriel; Sieber, Cornel; Volkert, Dorothee; Kiesswetter, Eva (SPRINGER, 2018)

Nutritional status according to the mini nutritional assessment (MNA)® as potential prognostic factor for health and treatment outcomes in patients with cancer - a systematic review - Torbahn, Gabriel; Strauß, Thomas; Sieber, Cornel; Kiesswetter, Eva; Volkert, Dorothee (BMC Cancer, 2020)
BACKGROUND: Patients with cancer have an increased risk of malnutrition which is associated with poor outcome. The Mini Nutritional Assessment (MNA®) is often used in older patients with cancer but its relation to outcome is not known. METHODS: Four databases were systematically searched for studies relating MNA-results with any reported outcome. Two reviewers screened titles/abstracts and full-texts, extracted data and rated the risk of bias (RoB) independently. RESULTS: We included 56 studies which varied widely in patient and study characteristics. In multivariable analyses, (risk of) malnutrition assessed by MNA significantly predicts a higher chance for mortality/poor overall survival (22/27 studies), shorter progression-free survival/time to progression (3/5 studies), treatment maintenance (5/8 studies) and (health-related) quality of life (2/2 studies), but not treatment toxicity/complications (1/7 studies) or functional status/decline in (1/3 studies). For other outcomes - length of hospital stay (2 studies), falls, fatigue and unplanned (hospital) admissions (1 study each) - no adjusted results were reported. RoB was rated as moderate to high. CONCLUSIONS: MNA®-result predicts mortality/survival, cancer progression, treatment maintenance and (health-related) quality of life and did not predict adverse treatment outcomes and functional status/ decline in patients with cancer. For other outcomes results are less clear. The moderate to high RoB calls for studies with better control of potential confounders.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Malnutrition; Neoplasms; Nutrition assessment; Nutritional status; Prognosis; Systematic review